EVALUATION OF THE LEVEL OF DIGITALIZATION OF ENERGY FACILITIES - KAVUN, IVAN; ZAMULKO, ANATOLII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The methods for evaluating the digitalization of energy facilities are considered, which allow for effectively determining the level of implemented digitalization and planning further steps to ensure the readiness of energy systems for the implementation of digital technologies. The main approaches to evaluation are analyzed, including methods of technical, economic, and socio-environmental assessment, as well as methods based on big data. Special attention is given to identifying opportunities for further improvement of energy systems using digital technologies. The importance of a comprehensive approach to evaluation is emphasized, as it increases the effectiveness of energy facility operations by reducing costs and improving reliability. The relevance of this topic is also confirmed by the aforementioned research on digitalization, as well as the requirements of sustainable development, which task energy companies with not only reducing costs and improving the quality of energy supply but also contributing to environmental preservation by minimizing the impact on nature. The evaluation of the digitalization level of energy facilities will allow for identifying further steps in the implementation of digital solutions, as well as assessing the effectiveness of their integration and timely adjustments to the strategy to achieve the desired results. The digitalization of energy facilities includes the integration of information and communication technologies into the management and operation processes of energy enterprises, such as generating stations, distribution networks, energy storage systems, and energy consumers. Digital transformation is a crucial stage in the development of the power sector, involving the implementation of new technologies, principles, and processes. Digitalization should be a comprehensive process that starts with an assessment of the current state, a review of equipment, and ends with the creation of a step-by-step modernization plan, determining the relevant level (as of the time of the survey) to account for future workloads and the possibility of integrating existing equipment into the new digital system.
Keywords: digitalization; management; digitalization processes; methods; evaluation; digital transformation